2015
DOI: 10.1177/0888406415600770
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of IRIS STAR Legacy Modules Under Different Instructional Conditions

Abstract: The vast majority of special education teacher preparation programs in the United States incorporate the IRIS Center’s STAR Legacy modules into their coursework. Given the diversity of module content and ways in which the modules are employed, the purpose of this study was to explore the potential mediating effects of instructional context on learner outcomes. Using an experimental, pretest-posttest-maintenance design, 115 participants experienced three different IRIS modules (Peer-Assisted Learning Strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Success was verified through comparison of pretests and poststests scores, where significant improvement in nutrition knowledge occurred. Similarly, Sayeski et al. (2015) assessed the efficacy of IRIS STAR Legacy Modules which follows a flipped model by using pretest–posttest-maintenance design.…”
Section: Introductionmentioning
confidence: 99%
“…Success was verified through comparison of pretests and poststests scores, where significant improvement in nutrition knowledge occurred. Similarly, Sayeski et al. (2015) assessed the efficacy of IRIS STAR Legacy Modules which follows a flipped model by using pretest–posttest-maintenance design.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from the other three studies (Sayeski et al, 2015;Adnan, 2017;Almodaires et al, 2019) were mixed. Adnan (2017)'s statistical results revealed no significant difference between the EG and the CG on midterm/quizzes and final eportfolio scores; however, the EG achieved significantly higher essay scores.…”
Section: Academic Performance In a Flipped Classroommentioning
confidence: 92%
“…Almodaires et al (2019) found a significant difference among the three exam results in favor of the EG but no significant difference in the final grade. Sayeski et al (2015) found that students' learning outcomes were statistically significantly better in the flipped instructional condition than in the other two instructional conditions (homework and instructor facilitated) for a Peer-Assisted Learning Strategies (PALS) module (PALS is a reading strategy for Grades 2-6). However, there were no statistically significant differences for the Classroom Management and Accommodations modules.…”
Section: Academic Performance In a Flipped Classroommentioning
confidence: 98%
“…Students who complete readings prior to class tend to understand instructional material better and are more prepared for class (Gurung, 2003;Narloch et al, 2006). Completing work outside of class may also contribute to student satisfaction and sense of self-determination (Sergis et al, 2018).…”
Section: Beyond the Basics: Adapting An Open Textbook To Accommodate mentioning
confidence: 99%